Development of a Coding-Integrated Project-Based Learning (PJBL) Module to Enhance Digital Literacy Among Elementary School Students - Anggita Silvi Zahrotus Jannah; Faridahtul Jannah; Shofia Hattarina; Ribut Prastiwi Sriwijayanti (International Journal of Educational Evaluation and Policy Analysis, 2026)
This study aimed to (1) develop a Project-Based Learning (PjBL) model integrated with coding activities that aligns with the learning characteristics of elementary school students, (2) examine the validity of the developed model through expert evaluations, and (3) investigate its effectiveness in improving students’ digital literacy. The research employed a Research and Development (R&D) approach using the ADDIE framework, consisting of Analysis, Design, Development, Implementation, and Evaluation phases. The study was conducted in a fifth-grade classroom at SDN Ambulu II. Data were collected through classroom observations, interviews, expert validation sheets, student response questionnaires, and pre-test and post-test assessments. Descriptive quantitative analysis was used to interpret the data, while the N-Gain index measured improvements in students’ digital literacy. The results indicated that the coding-integrated PjBL model was highly feasible, with validity scores of 95% from material experts and 95.8% from media experts. Practitioners rated the model’s practicality at 95%, while student responses reached 99%, indicating high acceptance. The effectiveness analysis produced an N-Gain score of 0.76, categorized as high, demonstrating a significant improvement in students’ digital literacy. These findings suggest that the coding-integrated Project-Based Learning model is valid, practical, and effective for supporting elementary school IPAS learning and enhancing students’ digital literacy.